2015
DOI: 10.1111/pops.12285
|View full text |Cite
|
Sign up to set email alerts
|

Some Dare Call It Conspiracy: Labeling Something a Conspiracy Theory Does Not Reduce Belief in It

Abstract: “Conspiracy theory” is widely acknowledged to be a loaded term. Politicians use it to mock and dismiss allegations against them, while philosophers and political scientists warn that it could be used as a rhetorical weapon to pathologize dissent. In two empirical studies conducted on Amazon Mechanical Turk, I present an initial examination of whether this concern is justified. In Experiment 1, 150 participants judged a list of historical and speculative theories to be no less likely when they were labeled “con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
72
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 32 publications
3
72
2
4
Order By: Relevance
“…This likely made the conspiratorial identity of our material more salient, which might have enhanced its impact on our participants’ perceptions. A comparative view of our results and those of Wood (), thus, raise the interesting question about the respective weight that the label versus the content of conspiracy theories may have on people's perceptions. Subsequent studies could test these two effects orthogonally, if technically possible.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This likely made the conspiratorial identity of our material more salient, which might have enhanced its impact on our participants’ perceptions. A comparative view of our results and those of Wood (), thus, raise the interesting question about the respective weight that the label versus the content of conspiracy theories may have on people's perceptions. Subsequent studies could test these two effects orthogonally, if technically possible.…”
Section: Discussionmentioning
confidence: 60%
“…These results allow us to go further than the conclusions drawn by a relatively more indirect investigation of the hypothesis of conspiracy theories as a social stigma (see Wood, ). Wood () tested whether the mere use of the label “conspiracy theory” produces a negative effect on the credibility of an idea, which could be taken to provide evidence for the discrediting power behind the label “conspiracy theory” (Husting & Orr, ), and by extension, for the stigma attached to conspiracy theories. In his experiments labeling written contents (i.e., conspiracy claims, confirmed historical conspiracies, and information from a bogus news article) as “conspiracy theories” versus “ideas,” did not have an effect on their perceived veracity.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The exact effect the term “conspiracy theory” and its variants have is open for debate. Some people are clearly repulsed by these terms, while others are attracted to them (see Wood, ). Nonetheless, conspiracy theories are a controversial subject (Bjerg & Presskorn‐Thygesen, ; Smallpage, ) which can arouse passions both in and out of academia (Cullen, ; Lewandowsky, ).…”
Section: Definitionsmentioning
confidence: 99%
“…But, since most research has focused on the causes rather than the consequences of conspiracy theorizing, much more work is needed. For example, there is surprisingly little research into how people who espouse conspiracy theories are viewed, and whilst some research has revealed that people fear social exclusion from expressing conspiracy beliefs (Lantian, Muller, Nurra, Klein, Berjot & Pantazi, ), one study suggests that labelling statements as “conspiracy theories” may not lower their perceived credibility (Wood, ). Future research could examine the social consequences that face people who adopt conspiracy theories.…”
Section: Definitionsmentioning
confidence: 99%